Environmental effect of steam on crack closure mechanisms of a 9–12% Cr ferritic/martensitic steel. (March 2020) - Fischer, T.; Kuhn, B.
Highlights: Investigation of the threshold behavior of X20CrMoV12-1 from 300 °C to 600 °C in steam. Separation and quantification of the crack closure mechanisms in steam up to 400 °C. Analysis of the atmosphere impact on the crack closure mechanism and corrosion. Influence of the steam atmosphere on the life time potential of components. Abstract: In the present study the impact of steam atmosphere on the threshold value and the active crack closure mechanisms of the ferritic/martensitic steel X20CrMoV12-1 were investigated from 300 °C to 600 °C. This temperature range is of particular importance for flexible power plant operation. The flexibilized operating mode is necessary because of the increased share of renewable sources of energy included in the power grid. Modern thermal power plants must be capable to compensate fluctuations in residual load. This results in a fundamental change in loading and damage scenarios. The start-up and shut-down cycles as well as load fluctuations increased drastically compared to the past. As a consequence the hold time at constant high temperature decreases and the damage scenario changes from creep to fatigue dominated damage or depending on the operating conditions to creep fatigue interaction. Currently original design codes are of limited validity for the assessment of such loading scenarios. For this reason new design codes based on damage tolerance concepts are required to exploit the maximum component lifetime without reducing safety. It was demonstrated that the steam atmosphere leads to an increase in the threshold value in the relevant temperature range and thus offers additional lifetime potential. This increase in threshold with rising temperature was correlated with increasing oxide layer thickness. Furthermore the active crack closure mechanisms were separated and quantified up to 400 °C (limited by the determination of the intrinsic threshold value). In addition the impact of temperature and corrosion on the threshold value was separated and quantified despite superposition of several mechanisms.